Pengaruh Iklim Komunikasi Organisasi Terhadap Kinerja Karyawan Di PT. Flextronics Batam - wulandari, indri; Jibrael Rorong, Michael (LPPM Universitas Putera Batam, 2024)
The role of human resources (HR) is one of the most important resources in an organization. Many workactivities in the work environment experience problems which can result in a lack of coordination in organizinginformation or messages and tasks which are the needs of every employee, from superiors to subordinates,which sometimes do not work effectively. Situations like this affect employee performance at PT FlextronicsBatam. The purpose of this research is to determine the influence of the organizational communication climateon employee performance at PT Flextronics Batam and how much influence the organizational communicationclimate has on employee performance at PT Flextronics Batam. This research method uses a quantitativeapproach with data collection techniques through questionnaires. The results of this research show that 58,7%of the employee performance variable will be influenced by the independent variable, namely CommunicationOrganizational Climate. Meanwhile, the remaining 41,3% of employee performance variables will be influencedby other variables not discussed in this research.